Labor market on nursing and homecare as a significant “doing” on health - Forte, Benedita Pessoa; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2001)
The study identified the significant actions of “doing homecare,” and its importance to health, focussing intervention in the alternative environment. The functional concepts of cultural care of Leininger (1991) were used as an instrument of theoretical meaning to verify the meaning of the scientific actions which exist over home intervention. Experienced reports of four nurses who were doing homecare with 1000 families in Fortaleza-CE by private enterprise, identified of cultural care on health system. Is has been concluded that homecare has a significant “ doing” on health, as a served benefit with scientific consistency.